On the mechanism of graphitizing inoculation of cast irons - E. I. Marukovich; V. J. Stetsenko (Литьë и металлургия)
On the basis of physical and chemical investigation of the processes of graphite formation in cast iron alloy a suggestion was made that the main mechanism of graphitizing modification is a coagulation-crystallization one. It consists in coagulation of graphite lyosol into supercritically sized nucleuses with their following growth in conditions of increased carbon activity at silicium dissolution. It is shown that the main and direct role in the graphite nucleation process belongs to the elements — active dioxidizing and desulfurizing agents. The role of non-metallic impurities is mainly reduced to dispersive and adsorption protection of graphite nucleuses of supercritical size.